(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The problems of professional preparation of future teachers of initial classes are explored in the article. The question of drafting and application o f educational-cognitive tasks is lighted to work of students with the texts of textbook on the lessons of reading.